PENGARUH LINGKUNGAN KELUARGA,PENGHARGAAN FINANSIAL, DAN GENDER TERHADAP MINAT BERKARIR MENJADI AKUNTAN PUBLIK - Astina Ningsih, Baiq Nani (INVOICE : JURNAL ILMU AKUNTANSI, 2021)
This study aims to determine the influence of the Family Environment, Financial reward, And Gender Against the wishes of his Career to Be certified Public Accountants (Case Study On Accounting Students of the University Sarjanawiata Tamansiswa). The research method used is a quantitative method that is Multiple Regression Analysis. the sampling method using purposive sampling with a total sample of 127 people. The type of data used is primary data. Tools of analysis used in this research is the application of SPSS software 18.0. The results obtained are (1) the family environment significantly influence the interest into public accounting. (2) award financial have a significant positive impact interest to become a public accountant. (3) the influence of gender on student interest in a career as a public accountant in this study is not supported. This suggests that in this study, gender did not have a positive and significant impact on student interest in a career as a public accountant.Keywords: Public Accountants, Gender, family Environment, Award financial.